Contactless sensing of liquid marbles for detection, characterisation & computing. Issue 1 (28th November 2019) - Draper, Thomas C.; Phillips, Neil; Weerasekera, Roshan; Mayne, Richard; Fullarton, Claire; de Lacy Costello, Ben P. J.; Adamatzky, Andrew
Abstract : New liquid marble sensor exploits impedance to detect presence of liquid marbles, whilst also providing characterisation information. Abstract : Liquid marbles (LMs) are of growing interest in many fields, including microfluidics, microreactors, sensors, and signal carriers. The generation of LMs is generally performed manually, although there has recently been a burst of publications involving 'automatic marble makers'. The characteristics of a LM is dependent on many things, including how it is generated, it is therefore important to be able to characterise LMs once made. Here is presented a novel contactless LM sensor, constructed on a PCB board with a comb-like structure of 36 interlacing electrical traces, 100 μm wide and 100 μm apart. This cheap, scalable, and easy to use sensor exploits the inherent impedance (comprised of the electrical resistance, capacitive reactance and inductive reactance) of different LMs. With it, parameters of a LM can be easily determined, without interfering with the LM. These parameters are (1) particle size of the LM coating, (2) the concentration of a NaCl solution used as the LM core, and (3) the volume of the LM. Additionally, due to the comb-like nature of the sensor, the accurate positioning (down to the inter-trace spacing) of the LM can be ascertained. The new sensor has been shown to work under both static and dynamic (mobile) conditions. The capacitance of a LM was recorded to be 0.10 pF, which compares well with the calculated value of 0.12 pF.